2021
DOI: 10.1002/ps.6657
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide transcriptional response of the causal soybean sudden death syndrome pathogen Fusarium virguliforme to a succinate dehydrogenase inhibitor fluopyram

Abstract: BACKGROUND: Succinate dehydrogenase inhibitors (SDHIs) have been widely used to manage plant diseases caused by phytopathogenic fungi. Although attention to and use of SDHI fungicides has recently increased, molecular responses of fungal pathogens to SDHIs have often not been investigated. A SDHI fungicide, fluopyram, has been used as a soybean seed treatment and has displayed effective control of Fusarium virguliforme, one of the causal agents of soybean sudden death syndrome. To examine genome-wide gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…They are involved in essential www.nature.com/scientificreports/ cellular functions, such as nutrient uptake and metabolite extrusion 48,48 . In addition, a recent study 50 showed that in F.virguliforme, MFS conferred reduced sensitivity to fluopyram (fungicide). Other such abundant core families in Foa include proteins having the fungal-specific transcription factor domain.…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in essential www.nature.com/scientificreports/ cellular functions, such as nutrient uptake and metabolite extrusion 48,48 . In addition, a recent study 50 showed that in F.virguliforme, MFS conferred reduced sensitivity to fluopyram (fungicide). Other such abundant core families in Foa include proteins having the fungal-specific transcription factor domain.…”
Section: Discussionmentioning
confidence: 99%
“…The strobilurins inhibit respiration through interactions with the quinol oxidation site of cytochrome b , thereby blocking electron flow through complex III and reducing the development of the proton motive force required for ATP generation [20]. Resistance to these agents can occur through point mutations in the target proteins (reviewed by [21]) and MDR can result from overexpression of ABC [22] or MFS [23] efflux pumps. There is no evidence for resistance through overexpression of electron transport chain (ETC) subunits, which is not unexpected as they function in large multi-subunit complexes of defined stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…cerealis), Botrytis cinerea (B. cinerea), and Sclerotinia sclerotiorum with a unique mode of action. Up to now, 24 SDHIs have been commercialized, , and fungi resistance has developed because of the long-term or excessive application of SDHI fungicides. Therefore, novel SDHIs without cross-resistance are always necessary for modern plant protection.…”
Section: Introductionmentioning
confidence: 99%